Piper betel Crude Leaf Extracts with HOCl (Formulated by Natural Oxygenated Water) as Plant Pathogenic Fungi Control. Issue 1 (1st July 2022) - Musa, S A N C; Zain, W Z W M; Wahab, M Z Ab; Ramli, N W; Hamid, N; Saharuddin, S; Izan, N N
Abstract: The use of synthetic fungicide are affecting the health, disturbing the ecosystem of the environment and has develop resistance of many pathogenic fungi. This study aimed to investigate the antifungal activity of ethanolic Piper betel (P. betel) crude leaf extracts with HOCl formulated by natural oxygenated water against selected crop pathogenic fungi which are Fusarium spp. and Phakopsora euvitis fungi. The screening test was done using well diffusion technique where the parameter observed was the Percentage Inhibition Radial Growth (PIRG). The antifungal effects of P.betel crude leaf extract with formulated HOCl minimum inhibitory concentration (MIC) were further evaluated by micro broth dilution method and minimum fungicidal concentration (MFC) were tested by agar well method. Screening results showed the P.betel extracts with HOCl have potential to inhibit the fungi radial growth when compared to positive control Kencozeb M45. MIC and MFC results portrayed the extracts with formulated HOCl displayed fungicidal activity against both fungi in the range of 2500 µg/ml until 5000 µg/ml for Fusarium spp and Phapkopsora euvitis, respectively. To the best of our knowledge this is the only natural oxygenated water source in Malaysia and first reported with combination of Piper betel extract.